2017
DOI: 10.1007/s13197-017-2799-x
|View full text |Cite
|
Sign up to set email alerts
|

Organic acids as a freshness indicator for tofu (soybean curd)

Abstract: The aim of this study was to evaluate organic acids as potential indicators of tofu freshness. To achieve this, relationships between organic acids concentrations and the growth of microorganisms in fresh tofu were investigated. The levels of microorganisms (total bacterial count) and organic acids (phytic acid, oxalic acid, citric acid, lactic acid, formic acid and acetic acid) were analyzed in tofu (packed and unpacked) every 3 days during 15 days of storage at different temperatures (4, 10, and 25 °C). Orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
(30 reference statements)
1
2
0
Order By: Relevance
“…However, Cruz et al (30) found 128 mg of lactic acid per 100 mL on the first day, which increased to 306 mg per 100 mL during 28 days. Dominant acid in soy beverage sample in the present work was acetic acid, which is consistent with the research of other authors (29,31). High concentrations of acetic acid in yoghurts are generally connected with fermentation of lactose to lactic acid, and this is called the heterofermentative pathway of lactose produced by strains of bifidobacteria.…”
Section: Fatty Acid Profiles Of Probiotic Beverages Determined With Gc-ms Methodssupporting
confidence: 92%
“…However, Cruz et al (30) found 128 mg of lactic acid per 100 mL on the first day, which increased to 306 mg per 100 mL during 28 days. Dominant acid in soy beverage sample in the present work was acetic acid, which is consistent with the research of other authors (29,31). High concentrations of acetic acid in yoghurts are generally connected with fermentation of lactose to lactic acid, and this is called the heterofermentative pathway of lactose produced by strains of bifidobacteria.…”
Section: Fatty Acid Profiles Of Probiotic Beverages Determined With Gc-ms Methodssupporting
confidence: 92%
“…27 The content of several organic acids, which was determined by liquid chromatography-mass spectrometry (LC/MS) analysis, was reported to predict the freshness of tofu. 28 In our previous work, the concentration of several CCAs was found to increase by several times in tea drinks during their spoilage period, in which that of succinic acid had increased by 75 times. 26 The increase in CCA content is likely to be related to the boom in the TCA cycle of microorganisms in the process of deterioration of tea beverages.…”
mentioning
confidence: 85%
“…The concentrations of CCAs and their variations are regarded as important indicators for the ripeness, decay and fermentation of foods 27 . The content of several organic acids, which was determined by liquid chromatography–mass spectrometry (LC/MS) analysis, was reported to predict the freshness of tofu 28 . In our previous work, the concentration of several CCAs was found to increase by several times in tea drinks during their spoilage period, in which that of succinic acid had increased by 75 times 26 .…”
Section: Introductionmentioning
confidence: 99%